The visibility of breastfeeding as a sexual and reproductive health right: a review of the relevant literature - Carina Stone; Julie P. Smith (BMC, 2022)
Abstract Background Governments must protect and apply maximum feasible resourcing to the protection, promotion and support of breastfeeding in order to meet their international legal obligations with respect to the human rights of women and children. However, governments across the world have consistently failed in these duties. Breastfeeding has been notably absent from mainstream feminist advocacy on sexual and reproductive health rights ('SRH rights'). Why is there this lack of focus on breastfeeding in feminist advocacy in this area? This review seeks to identify the extent to which the protection, promotion and support of breastfeeding is visible within the SRH rights and the gender responsive budgeting literature. Method A cross-disciplinary single scoping literature review of online and other databases was conducted to yield final samples of eighty-seven publications from the SRH rights literature and forty-four publications from the gender responsive budgeting literature. These publications were searched for references to breastfeeding. Results Only 21% of the sexual and reproductive health rights literature and just one gender responsive budgeting publication sampled referenced the protection, promotion and support of breastfeeding. Where breastfeeding was mentioned in the publications reviewed it was, in general, brief and on the periphery of discussion. Conclusions Reviews of the SRH rights literature and the gender budgeting literature both reveal an overwhelming absence of meaningful analysis on breastfeeding. The lack of attention to breastfeeding in the gender advocacy space represents a lost opportunity to advocate for the alleviation of the economic and social constraints imposed on breastfeeding women and caregivers.